Longitudinal study of the dynamics of vaginal microflora during two consecutive menstrual cycles. - Guido Lopes Dos Santos Santiago (Public Library of Science (PLoS), 2011)
Background Although the vaginal microflora (VMF) has been well studied, information on the fluctuation of the different bacterial species throughout the menstrual cycle and the information on events preceding the presence of disturbed VMF is still very limited. Documenting the dynamics of the VMF during the menstrual cycle might provide better insights. In this study, we assessed the presence of different Lactobacillus species in relation to the BV associated species during the menstrual cycle, assessed the influence of the menstrual cycle on the different categories of vaginal microflora and assessed possible causes, such as menstruation and sexual intercourse, of VMF disturbance. To our knowledge, this is the first longitudinal study in which swabs and Gram stains were available for each day of two consecutive menstrual cycles, whereby 8 grades of VMF were distinguished by Gram stain analysis, and whereby the swabs were cultured every 7(th) day and identification of the bacterial isolates was carried out with a molecular technique. Methods Self-collected vaginal swabs were obtained daily from 17 non pregnant, menarchal volunteers, and used for daily Gram staining and weekly culture. Bacterial isolates were identified with tDNA-PCR and 16 S rRNA gene sequencing. Results Nine women presented with predominantly normal VMF and the 8 others had predominantly disturbed VMF. The overall VMF of each volunteer was characteristic and rather stable. Menses and antimicrobials were the major disturbing factors of the VMF. Disturbances were always accompanied by a rise in Gram positive cocci, which also appeared to be a significant group within the VMF in general. Conclusions We observed a huge interindividual variability of predominantly stable VMF types. The importance of Gram positive cocci in VMF is underestimated. L. crispatus was the species that was most negatively affected by the menses, whereas the presence of the other lactobacilli was less variable.